RANCANG BANGUN SAFETY GUARDING TABLE SAW MACHINE GUNA MENINGKATKAN PRODUKTIFITAS PADA PT. BENTENG API TECHNIC - Achmad Rizal Triandiko (LPPM Universitas Bina Bangsa, 2023)
Safety Guarding is a machine protective equipment that aims to minimize potential hazards contained in Table saw Machine. By reducing potential hazards that can eliminate operator working hours due to work accidents that result in reducing productivity in the Brick Form Department, PT. Technic Fire Fortress. By designing Safety Guarding, it is expected to overcome existing problems, by making direct observations and collecting statistical data on work accidents at PT. Benteng Api Technic as a support for research, conducting concept screening, specification identification, specification determination, prototype trials, and evaluating the results of the application of safety guarding table saw machines to get the expected results.There were 13 cases of work accidents in 2022 at PT. The Technic Fire Fortress due to lack of security on the machines was at risk, resulting in as much as 20 days of total lost work time. The operation Â of the Table Saw Machine was diverted to the use of Jigsaw as a woodcutting tool as an effort to reduce the number of work accidents, but the productivity of the Brick Form Department also decreased. With the implementation of safety guarding, namely to restore the original activity on the Table Saw Machine and increase productivity at PT. The previously declining Technic Fire Fortress. So that from this research an effective machine protection concept was produced to dispel unauthorized cases that cause work accidents, dispel material exposure from cutting activities, without reducing the performance ofÂ the Table Saw Machine, increaseÂ user safety and increase the company's reputation